2023
DOI: 10.1038/s41467-023-37240-2
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of astrocyte activity by the calcium sensor STIM1 restores long-term synaptic plasticity in female mice modelling Alzheimer’s disease

Abstract: Calcium dynamics in astrocytes represent a fundamental signal that through gliotransmitter release regulates synaptic plasticity and behaviour. Here we present a longitudinal study in the PS2APP mouse model of Alzheimer’s disease (AD) linking astrocyte Ca2+ hypoactivity to memory loss. At the onset of plaque deposition, somatosensory cortical astrocytes of AD female mice exhibit a drastic reduction of Ca2+ signaling, closely associated with decreased endoplasmic reticulum Ca2+ concentration and reduced express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 83 publications
(90 reference statements)
1
8
0
Order By: Relevance
“…But other candidates presenting similar sensitivity to heat and ROS, such as TRP Ankyrin 1, are likely to be rapidly integrated in the arsenal of Ca 2+ -permeable channels that could be probed for their therapeutic potential. In conclusion, this Symposium, which also engendered may fruitful discussions and opened the way to new collaborations among the participants (including many foreigner guests), confirmed that Italian Physiology is at the forefront of research in Ca 2+ signalling, as also proven by many other oral and poster presentations of the meeting ( Martinotti et al, 2019 ; Nesher et al, 2019 ; Badone et al, 2021 ; Lazzarini et al, 2022 ; Michelucci et al, 2022 ; Sforna et al, 2022 ; Arici et al, 2023 ; Lia et al, 2023 ).…”
Section: Discussionsupporting
confidence: 69%
“…But other candidates presenting similar sensitivity to heat and ROS, such as TRP Ankyrin 1, are likely to be rapidly integrated in the arsenal of Ca 2+ -permeable channels that could be probed for their therapeutic potential. In conclusion, this Symposium, which also engendered may fruitful discussions and opened the way to new collaborations among the participants (including many foreigner guests), confirmed that Italian Physiology is at the forefront of research in Ca 2+ signalling, as also proven by many other oral and poster presentations of the meeting ( Martinotti et al, 2019 ; Nesher et al, 2019 ; Badone et al, 2021 ; Lazzarini et al, 2022 ; Michelucci et al, 2022 ; Sforna et al, 2022 ; Arici et al, 2023 ; Lia et al, 2023 ).…”
Section: Discussionsupporting
confidence: 69%
“…It is worth mentioning that transcriptome analysis in astrocytes from AD patients revealed expression changes in 32 genes associated with Ca 2+ signaling (Simpson et al, 2011). Consistently, early astrocyte calcium dysfunction is found in different AD mouse models, with both hyperactivity and hyporesponsiveness reported (Kuchibhotla et al, 2009;Lines et al, 2022;Åbjørsbråten et al, 2022;Lia et al, 2023). Along this line, an attenuated astrocyte endfeet response to neuronal stimulation has been recently suggested to contribute to NVC impairment in APP mice, in which reactive oxygen species (ROS) were also involved (Li L. et al, 2021).…”
Section: Alzheimer's Diseasementioning
confidence: 83%
“…Stimulation‐elicited LTP is decreased by decoupling of astrocytes in the mouse hippocampus (Hösli et al, 2022 ). Astrocyte‐regulated LTP of the mouse somatosensory cortex is affected in the mouse model of Alzheimer's disease and the consequential reduction of astrocytic Ca 2+ signaling (Lia et al, 2023 ). The cognitive decline in aged mice is prevented in IP3KO mice with altered astrocytic calcium signaling (Guerra‐Gomes et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%